Atividade anti-inflamatória e antinociceptiva da N-Metil-Trans-4-Hidroxi-L-Prolina isolado das folhas de Sideroxylon obtusifolium - Aquino, Pedro Everson Alexandre de (2016)
Sideroxylum obtusifolium (Humb. Ex. Roem. & Schult) T. B. Penn (Sapotaceae) of common occurrence in South America, is known in the Northeast of Brazil as "Quixabeira". The decoctions from the stem bark and leaves are used in folk medicine as anti-inflammatory. The present study evaluated by in vitro and in vivo models the anti-inflammatory and antinociceptive effects of the compound N-methyl-trans-4-hydroxy-L-proline (NMP) isolated from the leaves of Sideroxylon obtusifolium. Male Swiss mice (25-30 g; n = 8-10) were used in the tests of formalin, abdominal contractions induced by acetic acid, capsaicin and von- Frey. Anti-inflammatory effects were investigated using the tests of paw edema and peritonitis, both induced by carrageenan. We investigated possible mechanisms of action of NMP through the pharmacological blockade by naloxone, yohimbine and glibenclamide. Furthermore, the inflamed legs by carrageenan were collected and then sent for histological and immunohistochemical assay for TNF-α, iNOS, COX-2 and NF-kB. The participation of neutrophils was verified by myeloperoxidase dosage (MPO) and the antioxidant activity was tested by the DPPH method. The results showed reductions of 35, 42 and 52% in the 1st phase (neurogenic) and of 30, 61 and 78% in the 2nd phase (inflammatory) of the formalin test, and of 34, 53 and 72% in the writhings /20 min induced by acetic acid at the doses of 25, 50 and 100 mg / kg, respectively (P <0.05). NMP (100 mg / kg) reduced the hyperalgesia in the capsaicin and Von-Frey tests (P <0.05). There was a reduction of edema after treatment with NMP at all periods (P <0.05). NMP decreased significantly the number of leukocytes infiltrate of the peritoneal cavity induced by carrageenan. The results of the in vitro tests showed reduced MPO activity (P <0.05) but there was no antioxidant effect in DPPH test. There were significant reductions in the number of immunostained cells to TNF-α, iNOS, COX-2 and NF-kB in the groups treated with NMP (P <0.05). The investigation of possible mechanisms of anti-inflammatory action and antinociceptive of NMP suggest the involvement of the vanilloid receptor TRPV1 and the participation of K + channels, ATP-dependent and discard the participation of opioids and α2-adrenergic receptors. The findings of this study indicate that NMP has significant anti-inflammatory and antinoceptive effects that can be favorable as pharmacological tool for the treatment of conditions in which these pathways are highlighted.